Knowledge, attitude, and oral hygiene practices among law students in Davangere City: A cross-sectional study - G A Babitha; K Shashanka Holla; Basavanagowda Patel; G M Prashant; Shobha Prakash (Wolters Kluwer Medknow Publications, 2023)
Aim: The aim of this study was to assess dental health awareness and oral hygiene practice among law students of R L Law College, Davangere, Karnataka. Materials and Methods: A questionnaire containing 30 questions, regarding basic knowledge, attitude, and practice was distributed among 150 Law students of R L Law college of Davangere, Karnataka, India. The data obtained were tabulated in Microsoft Excel and statistically analyzed in the Statistical Package for the Social Sciences (IBM Corporation) software. Results: In the present study, only 39.4% of the participants were aware of routine dental check-ups. 8.5% of the participants visited the dental clinic twice a year and 57% of the participants had never visited a dental clinic. 37.3% of the participants were aware of oral hygiene aids. 62% of the participants used a tongue cleaner routinely and 55.5% brushed their teeth using only horizontal brushing technique. 48.6% were aware that consuming tobacco causes cancer. Only 9.2% consumed tobacco in various forms. 49% of the participants felt that all dental procedures were painful and expressed fear. 81% of the students were unaware of dental fluorosis. 65.5% of the participants agreed that dental health education is important and 21.8% thought that it might be important. Inferential statistics using the Pearson Chi-square test showed that there was a statistically significant correlation between the responses and the Year of law degree the participant was pursuing. Conclusion: In the present study, law students have satisfactory knowledge about good oral hygiene practices and oral health care. However, the knowledge acquired must be transferred into daily practice. This can be achieved by a change in their attitude toward oral hygiene maintenance. The inclusion of oral health-oriented education programs in their curriculum would improve their knowledge along with behavior, and they would be a good model to the community. This study will help us in devising an outline for the oral hygiene education of Law students of our country based on their current attitude, knowledge, and oral hygiene practice.